2019
DOI: 10.1371/journal.pone.0213078
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miRNAs in acute myeloid leukemia quantified by Nextgen sequencing of whole blood samples

Abstract: New approaches are needed for understanding and treating acute myeloid leukemia (AML). MicroRNAs (miRs) are important regulators of gene expression in all cells and disruption of their normal expression can lead to changes in phenotype of a cell, in particular the emergence of a leukemic clone. We collected peripheral blood samples from 10 adult patients with newly diagnosed AML, prior to induction chemotherapy, and 9 controls. Two and a half ml of whole blood was collected in Paxgene RNA tubes. MiRNA was puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Such relationship is considered a hotspot for research, which motivated many groups to work on expression profiling of miRNAs in different cellular contexts and in different types of neoplasms (Peng and Croce, 2016;Liao et al, 2017;He et al, 2019). Interestingly, each type of leukemia had unique profile of expressed microRNA linked with specific translocation or genetic mutations (Zhang et al, 2009), and such patterns highlighted the potential to use such profiling strategy to discriminate between subtypes of leukemias as well as to predict disease progression (Chan et al, 2011;Pandita et al, 2019). Genes responsible for the production of miRNAs are first transcribed into hairpin structured precursor microRNA molecules, which then are processed to give rise into the mature miRNAs; 19-22-nt long (Bartel, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such relationship is considered a hotspot for research, which motivated many groups to work on expression profiling of miRNAs in different cellular contexts and in different types of neoplasms (Peng and Croce, 2016;Liao et al, 2017;He et al, 2019). Interestingly, each type of leukemia had unique profile of expressed microRNA linked with specific translocation or genetic mutations (Zhang et al, 2009), and such patterns highlighted the potential to use such profiling strategy to discriminate between subtypes of leukemias as well as to predict disease progression (Chan et al, 2011;Pandita et al, 2019). Genes responsible for the production of miRNAs are first transcribed into hairpin structured precursor microRNA molecules, which then are processed to give rise into the mature miRNAs; 19-22-nt long (Bartel, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…15,16,17 Some studies have demonstrated that certain miRNAs play an important role in certain malignant diseases such as AML with NPM1+/FLT3+ mutations. 18 One of the miRNAs associated with NPM1+/FLT3+ AML, miR-10a-5p showed the most statistically significant adjusted pvalue in the yield as well as the highest fold change. This miRNA had been described in patients with NPM1 mutations.…”
Section: Ilcregs: To Be or Not To Bementioning
confidence: 89%
“…Comparison of qPCR and microarray technology with deep sequencing results using the Illumina platform demonstrated the best correlation between the Agilent qPCR platform and the deep sequencing [ 76 , 77 ]. A recent study of global miRNA sequencing in AML samples showed an advantage to microarray analysis, since it removes the bias due to its specificity regarding the 5p or 3p strand of the gene that might have functional relevance [ 78 ]. These technologies have been extended to single cell RNA sequencing.…”
Section: Methodical Strategies and Specific Challenges Regarding Mmentioning
confidence: 99%